Measuring the Degree of Profit Management Practices in The Egyptian Banking Sector - Albatarni, Rana (The Arab Journal of Administration, 2023)
The aim of the research is to determine whether the banks listed on the Egyptian Stock Exchange practice profit management when preparing their financial statements. A descriptive and analytical approach was used, and the research community included banks listed on the Egyptian Stock Exchange, and a sample was selected from five banks listed, which are: (Commercial International Bank, Qatar National Bank, Egyptian Gulf Bank, and Kuwait Bank Al-Watani - Egypt, and the Housing and Development Bank), during the period between the two years (2015-2019). The annual reports and financial data published on the banks’ websites of the research sample were relied on to measure profit management practices and the calculation of optional accrual, and the hypotheses were tested using the statistical program SPSS version 24, using one sample t- test. The study found that banks listed on the Egyptian Stock Exchange practice profit management practices when preparing their financial statements, in both directions (up and down) and in different degrees, with the aim of increasing their profits to increase the remuneration of their board members or reduce their profits in order to evade taxes. The study recommended the necessity of spreading awareness by the guardianship and supervisory authorities, such as: the Egyptian Securities Authority, the Egyptian Stock Exchange and the Central Bank of Egypt, about the risks that may arise from profit management practices, especially in the long term, in addition to imposing sanctions on banks that prove their involvement in the practices of Profits management with all its methods and mechanisms.